THE COMPOSITION OF THE POETIC HOUSE IN THE POETRY OF THE AL WAHAB FAMILY - Saad Ali Saleh, Assist. Prof. Dr. Muhammad Nouri Abbas (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this research is to stand on the structural aspects of the poetic verse in the poetry of the Al Wahb family, who are the class of literary writers in the Abbasid era. Their literature received a great status, and they played a prominent role in the fields of literary life, so it is necessary to highlight their artistic and literary value, as their literature included aspects A composition such as the composition of the poetic verse and the composition of the literary text, as well as the artistic image in simile, metaphor, and metonymy, and their literature also included the sound level such as rhythm in poetry, poetic meter, rhyme, and internal music. From an introduction and five demands: (the predicate, the introduction, the delay, the omission, the interrogative, the appeal) in which I studied the syntactic level